(untitled) (Research, Society and Development, 2020)
Blended Learning emerges as the combination of two teaching modalities, classroom, in a traditional classroom, and online, using digital technologies. This proposes individual and group activities, promoting social exchanges between students, for the development of more meaningful learning. Therefore, a didactic proposal was elaborated, using Rotation by Stations, through investigative activities. This didactic proposal aims to relate Fractals with the study of Progressions with the help of Hybrid Teaching through Rotation by Seasons. In each station, the teaching methodology, Mathematical Research, was used, with the support of several resources, namely: GeoGebra software on the computer and smartphone; concrete material; collage of colored paper; and ruler with geometric instrument. This work aims to report the experimentation of this didactic proposal with the students of the second grade of High School, from a private school. Observation data and activity responses were collected. These were analyzed based on the theory of Hybrid Teaching. Through data analysis, it was identified that the proposal aroused the enthusiasm and curiosity of the students, who had more autonomy, became active in the construction of their own knowledge.